Translation of Horror - Simic, Amela (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2000)
AbstractThis article is a personal essay on how I started to translate and how my motives changed with the changes of life circumstances during war in ex-Yugoslavia.